Clinical, endoscopic, histopathological characteristics of patients with colorectal polyps - Endoscopy Gastroenterology Center, Hue University of Medicine and Pharmacy Hospital - Nguyen, Van Thu Ha; Nguyen, Phan Hong Ngoc (Tạp chí Y Dược Huế, 2022)
characteristics and the relationship between histopathology and some clinical and endoscopic features of colorectal polyps. Subjects: The patients aged 16 years old and older who were diagnosed with colon polyps at the Center for Gastroenterology - Endoscopy at Hue University of Medicine and Pharmacy Hospital from April 1st, 2020 to March 30th, 2021. Methods: Cross-sectional, retrospective description. Results: Study on 67 patients who were dianosiged as having colorectal polyps through endoscopy, in which, 48 patients underwent polypectomy and histopathology. The mean age is 55.8 ± 15.7 years old, the most common age group is ≥ 45 years old, male/female is 2/1. The time from symptoms onset to disease detection is usually 6 months to less than 1 year (37.4%). The common clinical symptoms: abdominal pain (83.6%), diarrhea (29.9 %), constipation (28.4%), dysentery syndrome (13.4%), bloody stools (31.3%). The position of polyps: anus (1.5%), rectum (47.8%), sigmoid colon (40.3%), descending colon (31.3%), transverse colon (22.4%), ascending colon (28.4) %), cecum (13.4%). The proportion of patients having ≥ 2 polyps (59.7%), 1 polyp (40.3%). Polyp sizes: 5 - < 10 mm (50.7%), < 5 mm (37.4%), ≥ 10 mm (11.9%) . The percentage of sessile polyps is higher than that of pedunculated polyps at each locations. Histopathological types: adenomatous polyps (60.4%), hyperplastic polyps (20.8%), malignant polyps (4.2%). Polyps with dysplasia (64.6%), mild – grade dysplasia (56.3%), severe-grade dysplasia (8.3%). The differences were statistically significant between the grade of dysplasia and the polyp size groups, between the histopathology and the grade of dysplasia (p < 0.05). Conclusions: Colorectal polyps are more common in patients ≥ 45 years old, male are much more of having than female. Abdominal pain, bloody stools are common symptoms. Common polyp phenotypes are sessile polyps, ≥ 2 polyps, 5 - < 10 mm in size, mainly in the rectum. Adenomatous polyps are the most common histopathological type, with the high rate of dysplasia.